Tuning the photocurrent responsive and resistive switching performances of stilbazolium/iodoargentate hybrids by modulating the aggregation mode among chromophores. Issue 4 (4th January 2023) - Chen, Jing-Jing; Huang, Chang-Qi; Yi, Hong-Mei; Lv, Zhou-Lin; Wu, Wei; Zheng, Hui-Dong; Li, Hao-Hong
Abstract : D–π–A stilbazolium-type dyes with substitutes ranging from –C2 H5 CN to –C2 H5 OH were incorporated with iodoargentates to generate three hybrids, whose photo/electrical performance will be enhanced greatly by modulating aggregation modes. Abstract : The study about the effect of the stacking mode on the photo/electrical performance of crystalline organic/inorganic hybrids will be beneficial for the design of new photo/electrically active materials. In this work, D–π–A stilbazolium-type chromophores bearing novel ortho-N -alkyl substituents were synthesized and incorporated with iodoargentates to generate three crystalline stilbazolium/iodoargentate hybrids, i.e., [(CMAMP)(Ag2 I3 )] n (1 ), [(HMAMP)(Ag2 I3 )] n (2 ), and [(HMAHP)2 (Ag5 I7 )] n (3 ). When the substitutes on the amine group range from –C2 H5 CN (for CMAMP + ) to –C2 H5 OH (for HMAMP + ), the same (Ag2 I3 ) n n − anions will be produced, and the π⋯π stacking interactions among stilbazoliums will be observed from absence to presence (weak head-to-head H-aggregation). Furthermore, when the substituent on the ortho-N of pyridine was also set as –C2 H5 OH (for HMAHP + ), more electron-rich (Ag5 I7 ) n 2 n − anion can be generated, and strong head-to-tail H-aggregation among HMAHP + cations will happen. The enhanced aggregation strengthening in 3 can lead to its larger blue-shift photoluminescence, higher photocurrent, and better resistive switching performance (much higher ON/OFF ratio of 4.51 × 10 2 ). Their binary resistive switching mechanism can be explained as the SCLC model, and the better photo/electrical performances of 3 stem from its stronger head-to-tail H-aggregations, more negatively charged (Ag5 I7 ) n 2 n − anion, and stronger (Ag5 I7 ) n 2n − –HMAHP + interaction. The highly delocalized π antibonding orbitals between the empty p-orbitals of ethylene in its LUMO of (HMAHP)2 2+ dimer of 3 also support this conclusion. The good structure–property correlation based on accurate structural information in these stilbazolium/iodoargentate hybrids will be beneficial for the design of next-generation memory devices.